Gemcitabine-Based Neoadjuvant Treatment in Borderline Resectable Pancreatic Ductal Adenocarcinoma: A Meta-Analysis of Individual Patient Data - Giovinazzo, Francesco; Soggiu, Fiammetta; Jang, Jin-Young; Versteijne, Eva; van Tienhoven, Geertjan; van Eijck, Casper H.; Han, Youngmin; Choi, Seong Ho; Kang, Chang Moo; Zalupski, Mark; Ahmad, Hasham; Yentz, Sarah; et al. (Frontiers in Oncology, 2020)
Background Non-randomized studies have investigated multi-agent gemcitabine-based neo-adjuvant therapies (GEM-NAT) in borderline resectable pancreatic ductal adenocarcinoma (BR-PDAC). Treatment sequencing and specific elements of neoadjuvant treatment are still under investigation. The present meta-analysis aims to assess the effectiveness of GEM-NAT on overall survival (OS) in BR-PDAC. Patients and Methods A systematic review and meta-analysis of individual participant data of all published articles on GEM-NAT for BR-PDAC were performed. The primary outcome was OS after treatment with GEM-based chemotherapy. In the Individual Patient Data analysis data were reappraised and confirmed as BR-PDAC according to NCCN guidelines based on provided radiological data. Results Six studies investigating GEM-NAT were included. Median overall survival ranged between 15·2 to 30·9 months. Data were available for 170 patients who received GEM-NAT. Pooled median patient-level OS was 24.5 (95%CI 20·4 – 28·5) at an Individual Patient Data level. Median survival in the subgroup of patients that underwent GEM-NAT, radiotherapy, and surgery was 27·8 (95% CI 23·5 – 32·0) months. Eighty-two (48.2%) patients experienced Grade III-IV toxicity. Resection and R0 rates were 62% and 88%, respectively. Conclusions The present study is the first meta-analysis combining IPD from a number of international centers with BR-PDAC in a homogenous cohort that underwent multi-agent gemcitabine neoadjuvant therapy (GEM-NAT) before surgery. GEM-NAT followed by surgical resection may improve survival and R0 resection in BR-PDAC. Also, GEM-NAT results in a good palliative option in non-resected patients because of progressive disease after neoadjuvant treatment. Results from randomized controlled trials (RCTs) are awaited to validate these findings.